A BLUEPRINT FOR APPRAISING AND GUIDING AUDIT STAFF. - Campfield, William L. (The Accounting Review, 1957)
Abstract Leaders in the accounting profession have become increasingly concerned about the supply of broadly trained persons for top positions in accounting firms. Notwithstanding, many firms have neglected to devise programs for systematic development of staff to assume the growing leadership responsibilities inherent in modem public accounting practice. Too often firms are made up of groups of specialists. This tends to narrow the individual staff member's experience so that by the time he has progressed in the firm to where he is a candidate for top management responsibilities, it may be too late to give him the broad experience requisite for the executive position. This paper has presented a broad format which might serve as a guide to a programmed appraisal and guidance by accounting firms of staff member development. A periodic and orderly appraisal of staff members eliminates the hit or miss subjective way in which staff progression is plotted in many firms. It has been well stated that in a professional service, "jobs are people." A planned program of staff appraisal and guidance will assure that able men be given opportunities to gain the sequential knowledge so necessary for progression to top decision-making positions. It will also assure a firm that its operational, training, and promotion policies will always be under adequate control.